Diversão em Juiz de Fora (MG): carnaval e futebol sob as lentes da Carriço Filme (1934-1956) - Romilda Aparecida Lopes (2021)
This thesis aims to analyze, in the light of the films produced by Carriço Filme, the entertainments in Juiz de Fora (MG) within 1934 and 1956, problematizing the narratives of the events connected to the amusement and the sociocultural aspects present in the films, seeking to capture the sense production processes on the social practices shown in the newsreels. The methodology used consisted, mainly, of the movie scenes analysis allied to secondary documentary data. It was also consulted, in lesser amount, personal and institutional files, in addition to memoirs. The interpretation of sources was guided by the identification of the most recurrent movie themes from the producer. Therefore, the films contained in the Cinejornal Carriço, elaborated by Cinemateca Brasileira, were considered. This publication has the descriptions of the newsreels made by the Cinemateca’s technicians. That said, analyzing the collected data, this thesis dedicates itself to analyze the movies about carnival and football. It is highlighted that these themes were selected during the documentary research regarding the Carriço Filme archive, as it has a great amount of material related to juiz-foranos’ entertainments. Furthermore, it was carried out, while this thesis was being written, the bibliographic research that could contribute for the analyses made in here. In summary, it is possible to notice that the movies regarding carnival link Juiz de Fora to a modern and progressive city ethos, highlighting it when compared to other towns in Minas Gerais. Besides from that, the film narrative seeks to reinforce clear divisions and dualities from “labour and non- labour”, “order and disorder”, underlining the power of religion, education and labour in the construction of an idea of man. Yet, the films mark a duality between “indoor carnivals”, the ones in clubs and lounges, and the “street carnival”. The football emphasises the images from the fans, in many cases, as an amorphous and numerous mass. However, the visual records show that, on the bleachers and on the matches’ surroundings, there were sections, distinctions and even greater enhances, this fact is transported to the script of the newsreels. Images of women, law- enforcement, sports press and children were also recurrent. Besides from that, there are exhibitions of the development in improvements and constructions from the sport clubs venues. The entertainment aspects had were exposed and associated to industrialization, urbanization and the city’s modernization. This was because, in both these cultural manifestations, it does not seem to have evidence capable of problematizing aspects as inequalities and urban inconsistencies in Juiz de Fora. Nevertheless, the images display how these manifestations would reinforce the status quo from certain groups, while others had their practices silenced.